Analysis of diabetes mortality characteristics among the residents in Fengxian District, Shanghai, 2012‒2021 - XU Haifeng; HU Yi; WU Zhenyu; CHEN Ying; DENG Zenan; XUE Ting; YUAN yuan; QIN Meng; TANG Haiying (Shanghai yufang yixue)
ObjectiveTo investigate the trends in diabetes mortality rate and the characteristics of decreased population in Fengxian District, Shanghai from 2012 to 2021.MethodsData from the death registration records of the residents in Fengxian District between 2012 and 2021, sourced from the Shanghai Death Surveillance System, were analyzed. Indicators such as the crude mortality rate due to diabetes, the standardized mortality rate, years of life lost (YLL), and the probability of premature death were estimated. Annual percentage change (APC) was used to analyze the temporal trends of mortality and the probability of premature death due to diabetes. Rate decomposition analysis was used to assess the contributions of demographic and non-demographic factors to diabetes mortality.ResultsFrom 2012 to 2021, there were 1 471 deaths due to diabetes in Fengxian District, with a crude mortality rate of 27.51/100 000 and a standardized mortality rate of 17.58/100 000. The crude mortality rate showed an overall increasing trend (APC=4.58%, Z=3.49, P<0.05). The potential years of life lost (PYLL) due to diabetes over this period amounted to 9 715 person-years, with a PYLL rate of 1.82 ‰, and the average years of life lost (AYLL) was 11.94 years. The probability of premature death was 0.41% (APC=3.36%, t=2.33, P<0.05). Both population aging and non-aging factors contributed to the increase in diabetes mortality, with overall contribution rates of 67.99% and 32.01%, respectively. Among men, the contribution rates were 60.57% and 39.43%, while among women, they were 79.43% and 20.57%, respectively.ConclusionFrom 2012 to 2021, both the crude mortality rate and the probability of premature death due to diabetes showed an upward trend among the residents in Fengxian District, with a higher YLL. Population aging was the main factor causing the increase in mortality rate, while non-demographic factors had a greater impact on the rise in diabetes mortality among men than that in women. Therefore, the management on male diabetes patients should be strengthened.